2013
DOI: 10.1007/s11538-013-9919-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control in the Treatment of Retinitis Pigmentosa

Abstract: Numerous therapies have been implemented in an effort to minimize the debilitating effects of the degenerative eye disease Retinitis Pigmentosa (RP), yet none have provided satisfactory long-term solution. To date there is no treatment that can halt the degeneration of photoreceptors. The recent discovery of the RdCVF protein has provided researchers with a potential therapy that could slow the secondary wave of cone death. In this work, we build on an existing mathematical model of photoreceptor interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…Colón Vélez et al (2003); Camacho et al (2010); Camacho and Wirkus (2013);Camacho et al (2014Camacho et al ( , 2016a and Camacho et al (2016c) have produced a series of spatially-averaged ordinary differential equation (ODE) models examining the rod trophic factor hypothesis. Their work suggests the importance of rod trophic factor to the survival of both rods and cones.…”
Section: Introductionmentioning
confidence: 99%
“…Colón Vélez et al (2003); Camacho et al (2010); Camacho and Wirkus (2013);Camacho et al (2014Camacho et al ( , 2016a and Camacho et al (2016c) have produced a series of spatially-averaged ordinary differential equation (ODE) models examining the rod trophic factor hypothesis. Their work suggests the importance of rod trophic factor to the survival of both rods and cones.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies in mouse models have shown that cone death often commenced after the end of the major phase of rod death (occurring many months after rod degeneration) challenging the hypothesis of the liberation of a toxic factor [23-24]. Finally, the model incorporates the role of the RdCVF as a direct connection from rods to cones [3,20,45]. RdCVF is produced by both types of rods, R n and R s , and its presence and release by the rods does not hinder or benefit the functionality or viability of rods [46-47].…”
Section: Methodsmentioning
confidence: 99%
“…A second theory that gathered a lot of popularity comes from the idea that rods produce some kind of signal/protein that is essential for keeping cones alive. Consequently, the disappearance of rods would deprive the cones of this signal/protein and trigger their degeneration [3,18-20]. This theory is supported by various experiments on mice and rats and led to the discovery of the Rod-derived Cone Viability Factor (RdCVF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the sufficient conditions for the existence of optimal control are satisfied (see Theorem 4.1 in [Fleming and Rishel, 1976]). The similar exercises of proving the existence of optimal control based on Theorem 4.1 in [Fleming and Rishel, 1976] are referred to [de Pillis et al, 2008], [Jang et al, 2011], [Camacho et al, 2014], and [Blayneh et al, 2009].…”
Section: Preliminariesmentioning
confidence: 99%